Manual thrombectomy in Primary Percutaneous Coronary Intervention via the Transradial Approach: A case report - Kabir, CM Shaheen; Haq, M Mahshid; Haq, M Maksumul (University Heart Journal, 2017)
The main goal of primary percutaneous coronary intervention (PPCI) is to achieve not only restoration of flow in the epicardial coronary artery, but also reperfusion at the level of myocardial tissue. Distal embolization is a possible complication of PPCI leading to lack of myocardial reperfusion and microvascular injury. Thrombus aspiration during PPCI has been proposed to prevent embolization. Although the use of thrombectomy devices to aspirate thrombus during primary PCI is not used routinely, there is growing evidence suggesting the use of thrombus aspiration catheters during PCI. We are reporting the case of a 53-year-old diabetic, hypertensive woman presenting with acute infero-posterior ST elevation myocardial infarction (STEMI) with right ventricular infarction. She underwent diagnostic coronary angiogram through transradial approach which revealed total occlusion of mid right coronary artery (RCA). Multiple runs of aspiration were performed using Diver Aspiration Catheter-6F and thrombus was aspirated from RCA. After successful thrombus aspiration, dramatic improvements in both coronary flow and ST-segment resolution were achieved. University Heart Journal Vol. 11, No. 2, July 2015; 90-93